Epidemiology of asthma in adults living in the Silesian voivodeship according to secondary epidemiological data - Ewa Niewiadomska; Małgorzata Kowalska (Nofer Institute of Occupational Medicine, 2017)
Background: Asthma is a serious public health challenge because of the increasing number of people with a new diagnosis and consequently the increasing costs of medical treatment (direct and indirect). The aim of this study is to analyze available epidemiological data with respect to their spatial and temporal variability in the Silesian voivodeship. In addition, the costs incurred by the National Health Fund (Narodowy Fundusz Zdrowia - NFZ) in treating asthmaic patients are analyzed. Material and Methods: The epidemiological descriptive study concerns adult inhabitants of the Silesian voivodeship with asthma diagnosed under the health service delivery system, financed by NFZ, as well as diagnossis and/or hospitalization registed in the routine register run by the NFZ in Katowice. Crude and standardized incidence and prevalence rates are calculated and their changes are evaluated. Spatial variability in districts is evaluated as well and costs incurred by NFZ are revealed. Results: In the years 2006-2010 the standardized rate of asthma remained at a high level of 392.3-469.6/100 000 inhabitants. Greater values were related to women than to men, as well as to inhabitants of districts located in the central and southern parts of the Silesian voivodeship. A slight decrease in the values of crude prevalence rates, from 52/100 000 inhabitants to 42/100 000, is reported. The annual cost of new cases treatment is 17 million PLN while the annual cost of all hospitalizations is at the level of 10 million PLN. Conclusions: Variability of incidence and prevalence due to asthma in the Silesian voivodeship is observed. An attempt at explaining this diversity requires in-depth research. A slight decrease in the values of both rates over time indicates less significant reduction in expenditure devoted to hospital treatment of asthmatic patients. Med Pr 2017;68(4):479-489